2013
DOI: 10.1111/pme.12002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Frequencies (2–3 Days/Week) of Aquatic Therapy Program in Adults with Chronic Low Back Pain. A Non-Randomized Comparison Trial

Abstract: Eight weeks of aquatic therapy program decrease levels of back pain and disability, increase quality of life, and improve health-related fitness in adults with chronic low back pain without effects in body composition. A dose-response effect was observed in some parameters, with greater benefits when exercising 3 days per week compared with 2 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 44 publications
1
55
0
7
Order By: Relevance
“…Baena-Beato, Arroyo-Morales, Delgado-Fernández, Gatto-Cardia, Artero (2013) reported that exercises in water therapy reduce back pain and also help to improve the quality of life and health in adults with chronic low back pain. A similar conclusion was reached by Svedenhag (1992), who determined aqua aerobics as very effective in reducing pain in patients with arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Baena-Beato, Arroyo-Morales, Delgado-Fernández, Gatto-Cardia, Artero (2013) reported that exercises in water therapy reduce back pain and also help to improve the quality of life and health in adults with chronic low back pain. A similar conclusion was reached by Svedenhag (1992), who determined aqua aerobics as very effective in reducing pain in patients with arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the existing physical therapy recourses, aquatic and land physical therapy can be considered to be a growing resource with several benefits and tailored to the daily life of each patient. The aquatic technique uses warmed pools for therapeutic ends and is a widely used as a resource for the rehabilitation of several pathologies [1][2][3][4][5][6][7]. The benefits provided by the aquatic environment have mostly to do with the physical properties of the water, such as buoyant forces, hydrostatic pressure and viscosity, which exert therapeutic and physiological properties upon the immersed body [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the literature revealed an improvement in trunk muscle strength after specific exercises on land and in water [1,6,28,29]. One of these studies was carried out by Baena-Beato, who evaluated the effects of different program frequencies (two or three weekly sessions) of aquatic therapy for patients with lumbar pain [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One alternative treatment is water therapy. 12,13,14 This usually involves some exercise while the buoyancy of the water reduces the spinal load (defined herein as the gravitational burden of the upper torso, head, and arms on the lumbar spine). Studies discussed herein 12,13,14 suggest that, with adequate frequency and duration of treatment, water therapy can be beneficial in the treatment of low back pain.…”
mentioning
confidence: 99%